2002
DOI: 10.1021/ja0269082
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Emission and Its Switching in Fluorescent Organic Nanoparticles

Abstract: A new class of organic nanoparticles (CN-MBE nanoparticles) with a mean diameter of ca. 30-40 nm, which exhibit a strongly enhanced fluorescence emission, were prepared by a simple reprecipitation method. CN-MBE (1-cyano-trans-1,2-bis-(4'-methylbiphenyl)ethylene) is very weakly fluorescent in solution, but the intensity is increased by almost 700 times in the nanoparticles. Enhanced emission in CN-MBE nanoparticles is attributed to the synergetic effect of intramolecular planarization and J-type aggregate form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

40
1,072
4
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,878 publications
(1,134 citation statements)
references
References 47 publications
40
1,072
4
4
Order By: Relevance
“…A distorted geometry (trans-conformation) would favour non-radiative processes, whereas the more planar geometry (cis-1•2ClO 4 ) would increase radiative processes, as observed previously. 15,19 Furthermore, the photoluminescence (PL) spectra of cis-1•2ClO 4 and trans-1•2ClO 4 in CH 3 CN-H 2 O mixtures with various water contents were investigated (Fig. S11).…”
Section: This Journal Is © the Royal Society Of Chemistry 2014mentioning
confidence: 99%
“…A distorted geometry (trans-conformation) would favour non-radiative processes, whereas the more planar geometry (cis-1•2ClO 4 ) would increase radiative processes, as observed previously. 15,19 Furthermore, the photoluminescence (PL) spectra of cis-1•2ClO 4 and trans-1•2ClO 4 in CH 3 CN-H 2 O mixtures with various water contents were investigated (Fig. S11).…”
Section: This Journal Is © the Royal Society Of Chemistry 2014mentioning
confidence: 99%
“…[1][2][3][4] Top-down and bottom-up approaches have been applied to manufacture FNPs from graphene, carbon nanotubes, and polymers. [5] However, for organic compounds, FNPs from condensation reactions as well as carbonization and dehydration systems are the best choice due to their simple manufacturing method.…”
Section: Introductionmentioning
confidence: 99%
“…Kasai and Nakanishi et al first reported that the fluorescence spectra of perylene nanocrystals, which were prepared by the reprecipitation method, depended on their size, and the fluorescence spectra of the nanoparticles differ from that of the bulk crystals [2,3]. There are many reports about organic nanoparticles in the past decade [4][5][6][7]. They proposed lattice softening of the nanoparticles as a cause of the size-dependent optical properties.…”
Section: Introductionmentioning
confidence: 99%